Analysis of International Claims in the Banking Sector: Implications for Islamic Finance in the Digital Age: Analisis Klaim Internasional pada Sektor Perbankan: Implikasi Keuangan Syariah di Era Digital - Fadil, Ahmad; S, Nawewi (JEIZA : Jurnal Ekonomi Islam Az-Zain, 2024)
Global digital transformation has changed the dynamics of international claims in the banking sector, presenting unique challenges for Islamic finance in ensuring compliance with Shariah principles. This study aims to understand how digitalization affects international claims in the banking sector and its implications for Islamic finance. The method used is secondary data analysis from banks' annual reports, international statistical data, and related scientific publications, with an observation period from the second quarter to the fourth quarter of 2023. The results showed that international claims in all sectors were relatively stable, with significant increases in the non-bank sector and the private non-financial sector. Claims on the banking sector experienced a slight decline before stabilizing again. The implications of the findings indicate the need for Islamic banks to strengthen Shariah compliance, diversify international portfolios, and develop new services to maintain stability and growth in the digital era